Emergencies and Sanitary Rules in Coronavirus Times: an Analysis between Brazil and Mexico - Cobos Campos, Amalia Patricia; Reckziegel, Janaína (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
The present study has the theme of global health emergencies, dealing especially with the role of the National Health Surveillance Agency in Brazil and the Secretariat of Health in Mexico in the current situation of the Coronavirus. In this sense, actions at the global level to combat global health emergencies and the treatment they have received in the country are discussed. For that, we used a qualitative methodology, with bibliographic and normative research. As a result, it is clear that although there are international regulations in the fight against emergencies, Brazil and Mexico do not have adequate legislation, having created only emergency regulations.